What is normal progress in the first stage of labour? A vignette study of similarities and differences between midwives and obstetricians. (October 2016) - Romijn (MSc.), A.; Muijtjens (dr. ir.), A.M.M.; de Bruijne (dr.), M.C.; Donkers (dr.), H.H.L.M.; Wagner (prof. dr.), C.; de Groot (prof. dr.), C.J.M.; Teunissen (dr.), P.W.
Abstract: Objective: intrapartum referrals are high-risk situations. To ensure patient safety, care professionals need to have a shared understanding of a labouring woman's situation. We aimed to gain insight into similarities and differences between midwives and obstetricians in the assessment of a prolonged first stage of labour and the decision to refer a woman to a clinical setting in the Netherlands. Design: factorial survey. Setting: in the Netherlands, the main caregivers for women with low risks of pathology are primary-care midwives working in the locality. Approximately half of all women start labour under supervision of primary-care midwives. Roughly 40% of these women are referred to a hospital during labour, where obstetricians take over responsibility. In 2013, the reason for referral for 5161 women (14.1% of all referrals during labour) was a prolonged first stage of labour. Participants: respondents consisted of primary-care midwives ( N =69), obstetricians ( N =47) and hospital based midwives, known as clinical midwives ( N =31). Measurements: each respondent assessed seven hypothetical vignettes. The assessment of a prolonged first stage of labour and the decision to refer a woman to a clinical setting based on this indication were used as outcome measures, rated on a 7-point Likert scale (1=very unlikely to 7=very likely). Data were analysed using a linear multilevel model with a two-level hierarchy. Findings: compared to primary-care midwives, obstetricians were more likely to define a prolonged first stage of labour when progress in cervical dilation was slow (b: 1.11; 95% CI: 0.66 – 1.57). The attributes parity, progress, intensity of uterine contractions and the woman's state of mind, were used by all three groups in the decision to refer a woman to clinical setting based on a prolonged first stage of labour. Key conclusion and implications for practice: we found relevant interprofessional differences and similarities in the assessment of a prolonged first stage of labour and consequent referral. Further interprofessional alignment of clinical assessments, for instance through interprofessional discussions and a review of professional guidelines, might help to improve collaborative care. Highlights: Assessment of a prolonged first stage of labour varies between care professionals in the Netherlands. Progress in cervical dilation is assessed differently by primary-care midwives and obstetricians. Referral is based on parity, progress, intensity of uterine contractions and the woman's state of mind. Differences need to be addressed to improve interprofessional collaboration.